The Impacts of Blue Economy Development on Coastal Community and Climate Crisis in Indonesia - Fadhlillah, Nibras (Masyarakat Ekonomi Syariah Bogor, 2025)
Over the last few decades, debates on environmental and economic growth issues have received special attention in various academic and policy discourses. Some argue that economic development has a significant impact on increasing persistent ecological degradation over time, while others view that using appropriate economic development tools and systems could harmonize government efforts to develop its economy, as well as ensure a more sustainable environment. The ongoing debates affect not only both economic development and environmental issues but also the emphasis of inclusivity on socioeconomic aspects. Initially, the Blue Economy development concept seeks to harmonize social, economic, and ecological elements in its economic development system. However, the socioeconomic aspect for small people – particularly marginal communities, is often forgotten during the implementation. This article is expected to analyze and explain the impacts of Indonesian Blue Economy development on its coastal community and fisherfolks. This article used a qualitative research method with desk/library research and qualitative interviewing as the data collection method. By critically examining the implementation of the Blue Economy in Indonesia, the article also aims to provide insight into the blue economy's impacts on the climate crisis in Indonesia.